Exploring students' preferences for open distance learning (ODL) during Covid-19 pandemic a case study among UiTM students / Anis Idayu Aziz ... [et al.] - Aziz, Anis Idayu; Omar, Siti Khadijah; Suhaimin, Mohd Faiez; Rozman Azram, Aina Athirah; Hanafi @ Mohd Ghani, Madaha (2021)
This research explored students' preferences for open distance learning (ODL) during COVID-19 pandemic. It aims to determine students' preferences for ODL as well as to explore contributing factors for such preferences. A quantitative method approach was adopted for the data collection, and IBM SPSS 25 was used to analyse the data. The questionnaire was distributed to 360 participants which involved three (3) Universiti Teknologi MARA (UiTM) campuses; UiTM Kelantan Campus, UiTM Tapah campus and UiTM Shah Alam. The findings showed that there were no significant differences in students' gender on ODL preferences. In addition, for item ODL preference 3, only the groups of faculties have significant difference compared to others. Furthermore, for item ODL preference 1, only the groups of ODL location and device preference have significant difference compared to the others. For the rest of the ODL preference, there was no significant difference between groups